Hubungan Latar Belakang Pendidikan PAUD terhadap Kepuasan Kerja Guru - Dea Elisabeth Lomaris; Dian Siregar; Delvira Napitupulu; Astri Fransiska Sibarani (Jurnal Ketopong Pendidikan, 2025)
This study aims to analyze the relationship between teacher educational background and the level of job satisfaction of Early Childhood Education (PAUD) teachers, as well as to compare the level of job satisfaction between teachers with linear and non-linear educational backgrounds. The study used a quantitative approach with a correlational and comparative design. The research subjects consisted of twenty PAUD teachers at Kindergarten X and Kindergarten Y Jakarta. Data were collected using the Teacher Job Satisfaction Questionnaire (TJSQ) which covers four factors of job satisfaction, namely individual factors, work environment, work, and outside of school. The results of the analysis showed that correlationally there was no significant relationship between educational background and job satisfaction of PAUD teachers. However, the results of the comparative analysis revealed a significant difference in the level of job satisfaction between teachers with linear educational backgrounds (bachelor of education) and teachers with non-linear backgrounds, where teachers with linear educational backgrounds showed a higher level of job satisfaction. This finding indicates that educational background does not function as a direct predictor of job satisfaction correlationally, but plays a role in differentiating the level of job satisfaction between groups of teachers. This research provides an empirical contribution in enriching the study of job satisfaction of PAUD teachers by emphasizing the importance of differentiating correlational and comparative analysis approaches in interpreting the influence of educational background, as well as being the basis for consideration in developing recruitment policies and professional development of PAUD teachers.